Characterization, expression patterns, and transcriptional responses of three core RNA interference pathway genes from Ostrinia nubilalis. (February 2021) - Cooper, Anastasia M.W.; Song, Huifang; Shi, Xuekai; Yu, Zhitao; Lorenzen, Marcé; Silver, Kristopher; Zhang, Jianzhen; Zhu, Kun Yan
Graphical abstract: Highlights: The O. nubilalis orthologs of Ago2, Dcr2, and R2D2 were sequenced and characterized. Transcripts of all three genes were detected in all stages and tissues. Comparison of evolutionary distances for domains revealed significant variations. Injection of ds GFP had no effect on Ago2, Dcr2, or R2D2 expression. Ingestion of ds GFP could induce up/down-regulation of some transcripts. Abstract: RNA interference (RNAi) is commonly used in the laboratory to analyze gene function, and RNAi-based pest management strategies are now being employed. Unfortunately, RNAi is hindered by inefficient and highly-variable results when different insects are targeted, especially lepidopterans, such as the European corn borer (ECB), Ostrinia nubilalis (Lepidoptera: Crambidae). Previous efforts to achieve RNAi-mediated gene suppression in ECB revealed low RNAi efficiency with both double-stranded RNA (dsRNA) injection and ingestion. One mechanism that can affect RNAi efficiency in insects is the expression and function of core RNAi pathway genes, such as those encoding Argonaut 2 (Ago2), Dicer 2 (Dcr2), and a dsRNA binding protein (R2D2). To determine if deficiencies in these core RNAi pathway genes contribute to low RNAi efficiency in ECB, full-length complementary DNAs encoding OnAgo2, OnDcr2, and OnR2D2 were cloned, sequenced, and characterized. A comparison of domain architecture suggested that all three predicted proteins contained the necessary domains to function. However, a comparison of evolutionary distances revealed potentially important variations in the first RNase III domain of OnDcr2, the double-stranded RNA binding domains of OnR2D2, and both the PAZ and PIWI domains of OnAgo2, which may indicate functional differences in enzymatic activity between species. Expression analysis indicated that transcripts for all three genes were expressed in all developmental stages and tissues investigated. Interestingly, the introduction of non-target dsRNA into ECB second-instar larvae via microinjection did not affect OnAgo2, OnDcr2, or OnR2D2 expression. In contrast, ingestion of the same dsRNAs resulted in upregulation of OnDcr2 but downregulation of OnR2D2 . The unexpected transcriptional responses of the core machinery and the divergence in amino-acid sequence between specific domains in each core RNAi protein may possibly contribute to low RNAi efficiency in ECB. Understanding the contributions of different RNAi pathway components is critical to adapting this technology for use in controlling lepidopteran pests that exhibit low RNAi efficiency.